Circumscribing the prostitute : the rhetorics of intertexuality, metaphor, and gender in Jeremiah 3.1-4.4 - Shields, Mary E. (Journal for the study of the Old Testament. Supplement series, 2004)
In Jeremiah 3.1-4.4 the prophet employs the image of Israel as God's unfaithful wife, who acts like a prostitute. The entire passage is a rich and complex rhetorical tapestry designed to convince the people of Israel of the error of their political and religious ways, and their need to change before it is too late. As well as metaphor and gender, another important thread in the tapestry is intertextuality, according to which the historical, political and social contexts of both author and reader enter into dialogue and thus produce different interpretations. But, as Shields shows in her final.